2018
DOI: 10.1371/journal.pone.0205593
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, interest, and anticipated barriers of pre-exposure prophylaxis uptake and adherence among gay, bisexual, and men who have sex with men who are incarcerated

Abstract: Criminal justice (CJ) settings disproportionately include populations at high risk for acquiring HIV, and CJ-involved individuals are often at the intersection of multiple overlapping risk factors. However, few studies have examined attitudes about pre-exposure prophylaxis (PrEP) among incarcerated men who have sex with men (MSM). This study explored interest in, knowledge of, and barriers to PrEP uptake among gay, bisexual, and other men who have sex with men at the Rhode Island Department of Corrections. Usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 32 publications
2
26
0
Order By: Relevance
“…Social factors related to poverty that limit women's access to antiretroviral therapy [44] may also impact PrEP prioritization: a 2017 review noted that ''unemployment, unstable housing, and food insecurity may render accessing PrEP and taking PrEP as unimportant if women are unable to fulfill their basic needs for food and shelter'' [45]. Another setting in which accessing PrEP may be deprioritized is for MSM who are released from incarceration: one study participant stated, ''When you go home you have so much to do… you have to go back to welfare to get food stamps… so much different stuff… you're not really going to be thinking about 'I've got to go to the doctor's [office] right away to get my PrEP''' [46]. Competing priorities have also been identified as major barriers to healthcare in general among homeless adults, for whom meeting basic needs for food, shelter, and safety outweigh healthcare needs [47].…”
Section: Low Perception Of Hiv Risk As a Barrier To Prep Uptakementioning
confidence: 99%
See 2 more Smart Citations
“…Social factors related to poverty that limit women's access to antiretroviral therapy [44] may also impact PrEP prioritization: a 2017 review noted that ''unemployment, unstable housing, and food insecurity may render accessing PrEP and taking PrEP as unimportant if women are unable to fulfill their basic needs for food and shelter'' [45]. Another setting in which accessing PrEP may be deprioritized is for MSM who are released from incarceration: one study participant stated, ''When you go home you have so much to do… you have to go back to welfare to get food stamps… so much different stuff… you're not really going to be thinking about 'I've got to go to the doctor's [office] right away to get my PrEP''' [46]. Competing priorities have also been identified as major barriers to healthcare in general among homeless adults, for whom meeting basic needs for food, shelter, and safety outweigh healthcare needs [47].…”
Section: Low Perception Of Hiv Risk As a Barrier To Prep Uptakementioning
confidence: 99%
“…At the individual level, there are simple logistical constraints to accessing PrEP, exacerbated by socioeconomic inequalities. For example, individuals may experience difficulty in getting to the clinic [74] due to lack of transportation [46] or time constraints [75,76]. A 2016 National Survey on HIV in the Black community found that 38% of 787 participants were more than one hour's drive from a PrEP provider.…”
Section: Lack Of Access To Medical Care As a Barrier To Prep Uptakementioning
confidence: 99%
See 1 more Smart Citation
“…People who are incarcerated have a prevalence of HIV that is 2.4 times that of the general population [1] and postrelease is known to be a time of increased engagement in high-risk HIV behaviors (e.g. return to drug use and condomless sex) [2,3,4,5,6]. For example, one study found that previously incarcerated men had a higher frequency of condomless sex and sex while under the influence of drugs or alcohol relative to men who had never been incarcerated [7].…”
Section: Introductionmentioning
confidence: 99%
“…Despite its potential benefit, linkage to and use of PrEP among people who are CJ-involved has been limited and there have been numerous barriers to implementation. For example, knowledge about PrEP among those who are incarcerated remains low [6,15]. Other PrEP related barriers, including medication costs, stigma associated with PrEP, competing needs upon community reentry, concern for side effects and low perceived HIV risk, have also been documented [6; 16-18].…”
Section: Introductionmentioning
confidence: 99%